Informal Urbanisation: Dynamics Between Land Traffickers and the Mayor's Office of a Municipality on the Urban Periphery of Lima, Peru - Arriola Laura, Addier Giovanni (2025)
Informal urbanisation is a heterogeneous phenomenon; on one hand, there are informal neighbourhoods that have successfully implemented basic services and infrastructure at an accelerated rate, while others remain marginalised from basic State services. This study argues that the different levels of informal urbanisation are due to the type of land trafficker who runs the informal neighbourhood and the relationship of exchange of material and political resources that he establishes with the municipal mayor’s office. Thus, a political trafficker succeeds in establishing a resource exchange relationship with the municipal mayor, while an economic trafficker does not create the conditions for such an exchange. To investigate this, a comparative study was conducted of two urban informal neighbourhoods in the Ate district of Lima, Peru, which share common geographical and political characteristics but have experienced different levels of informal urbanisation due to the presence of distinct types of land traffickers. The study highlights that informal urbanisation processes are not solely explained by State capacities or clientelism generated by political elites but are also influenced by the actions of informal and illegal actors within civil society.